The Mental Health Consequences of the Recession: Economic Hardship and Employment of People with Mental Health Problems in 27 European Countries - Evans-Lacko, Sara; Knapp, Martin; McCrone, Paul; Thornicroft, Graham; Mojtabai, Ramin (PLOS ONE, 2013)
Objectives A period of economic recession may be particularly difficult for people with mental health problems as they may be at higher risk of losing their jobs, and more competitive labour markets can also make it more difficult to find a new job. This study assesses unemployment rates among individuals with mental health problems before and during the current economic recession. Methods Using individual and aggregate level data collected from 27 EU countries in the Eurobarometer surveys of 2006 and 2010, we examined changes in unemployment rates over this period among individuals with and without mental health problems. Results Following the onset of the recession, the gap in unemployment rates between individuals with and without mental health problems significantly widened (odds ratio: 1.12, 95% confidence interval: 1.03, 1.34). This disparity became even greater for males, and individuals with low levels of education. Individuals with mental health problems living in countries with higher levels of stigmatizing attitudes regarding dangerousness of people with mental illness were more vulnerable to unemployment in 2010, but not 2006. Greater agreement that people with mental health problems have themselves to blame, was associated with lower likelihood of unemployment for individuals with and without mental health problems. Conclusion These findings study suggest that times of economic hardship may intensify social exclusion of people with mental health problems, especially males and individuals with lower education. Interventions to combat economic exclusion and to promote social participation of individuals with mental health problems are even more important during times of economic crisis, and these efforts should target support to the most vulnerable groups.